Reconstruction of cultural views of 'reluctant' prevents criminal acts of gratification - Galih Puji Mulyono; Yusuf Eko Nahuddin; Lily Faradina; Sri Indah Cahyani (Faculty of Law, University of Merdeka Malang, 2022)
This study aims to reconstruct the